2017
DOI: 10.1016/j.biopha.2017.08.079
|View full text |Cite
|
Sign up to set email alerts
|

The role of radionuclide probes for monitoring anti-tumor drugs efficacy: A brief review

Abstract: Despite recent advances in the development of new therapeutic agents and diagnostic imaging modalities, cancer is still one of the main causes of death worldwide. A better understanding of the molecular signature of cancer has promoted the development of a new generation of anti-cancer drugs and diagnostic agents that specifically target molecular components such as genes, ligands, receptors and signaling pathways. However, intrinsic heterogeneity of tumors has hampered the overall success of target therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Evaluating the potential of [ 18 F]FLT-PET for assessing early response to therapy is a logical step, given the clear utility of [ 18 F]FDG-PET in this role in LC. The rationale for using [ 18 F]FLT-PET to assess therapies that selectively affect proliferation is especially compelling, as these treatments may inhibit proliferation without affecting either metabolic rate or causing tumour shrinkage [ 54 ]. Only 4 out of the 18 LC response assessment studies identified in this review did not observe some utility for [ 18 F]FLT in this role [ 28 , 29 , 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the potential of [ 18 F]FLT-PET for assessing early response to therapy is a logical step, given the clear utility of [ 18 F]FDG-PET in this role in LC. The rationale for using [ 18 F]FLT-PET to assess therapies that selectively affect proliferation is especially compelling, as these treatments may inhibit proliferation without affecting either metabolic rate or causing tumour shrinkage [ 54 ]. Only 4 out of the 18 LC response assessment studies identified in this review did not observe some utility for [ 18 F]FLT in this role [ 28 , 29 , 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study evaluating [ 18 F]FLT-PET to assess EGFR-TKI response found no correlation with CT measurements [ 42 ]. However, this observation may be due to utilisation of size measurements to assess EGFR-TKI; change in tumour size may be delayed or may not occur at all with this type of therapy, creating a discrepancy between these two different metrics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of radionuclide-facilitated diagnosis of BC is illustrated in Figure 2. A common radionuclide cancer therapy is composed of three interconnected parts: A cancer cell-surface specific targeting molecule, a synthetic binding molecule that can specifically bind to the targeting molecule (called a linker), and a radionuclide-labeled chelator that is linked to the binding molecule (Figure 2) (57)(58)(59). All these three parts plus the specific surface marker on the cancer cells ensure the radionuclides target BC with high specificity and a high affinity, excluding potential off-target effects.…”
Section: Radionuclide Diagnosis In Breast Cancermentioning
confidence: 99%
“…The suggested method shows that the shields reduce the noise induced by the 177 Lu and therefore enable longitudinal quantitative intratherapeutic imaging studies. To improve cancer therapy, there is a need for sensitive and quantitative molecular imaging techniques to follow therapeutic efficacy and progress of disease (1,2).…”
mentioning
confidence: 99%
“…In preclinical research, molecular imaging techniques such as PET help decipher the response to treatment in animal tumor models. Changes in proliferation, hypoxia, angiogenesis, and other factors important to tumor growth and survival can be monitored in vivo with PET tracers (2)(3)(4)(5). PET adds physiologic information that can have better prognostic value than measuring tumor size and volume with calipers or with morphologic imaging such as CT or MRI (6).…”
mentioning
confidence: 99%